Analysis of the relationship between tax revenue and gross value added in the Romanian economy - Victor Ogneru (Financial Studies, 2019)
Any government is interested in knowing, to a certain extent degree, the level of tax revenue at a given time in order to design public expenditures. On the other hand, this level of budget revenue is desirable to be sustainable, i.e. to be supported by the existing economi c conditions at a given moment. One way to estimate the expected revenues is the relationship of the tax bases with the main macroeconomic indicators. It is assumed that the main source of tax is gross value added in the economy. This article examines the nature of gross value added links with the tax revenue, on the one hand, and with the tax bases of each category of tax, on the other hand, in order to identify the best predictors of tax revenue for Romania. The analysis was carried out using multiple tim e series regressions in the cases of Romania and the standard (benchmark) states (Germany, France, the United Kingdom and Italy), respectively regressions on cross - sectional data in the case of Member States of the European Union.
Keywords: H20; C51; 330; tax revenue; macroeconomic analysis; public finance; econometric modeling; estimation